2017
DOI: 10.1016/j.jsurg.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Spacing, Naps, and Fatigue on the Acquisition and Retention of Laparoscopic Skills

Abstract: Spacing laparoscopic training over 3 consecutive days or weeks is superior to massed training, even if the massed training contains breaks. Breaks with sleep opportunity (i.e., lying, inactive, and muted sensory input) enhance performance over training with regular breaks and traditional massed training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…It has long been observed that spaced training can improve learning efficiency compared to massed training for many types of learning behaviors (Cepeda et al, 2008; Litman and Davachi, 2008), however, the extent to which this is true to motor learning has primarily been investigated in human subjects. Results have been mixed, with some studies showing a benefit of spaced training on motor learning (Kwon et al, 2015; Spruit et al, 2017) and some showing no benefit versus massed training (Nadeau et al, 2014; Wiseheart et al, 2017). The effect of spaced versus massed training and has never clearly been formally assessed for standard rodent rotarod learning, let alone motor gist learning.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been observed that spaced training can improve learning efficiency compared to massed training for many types of learning behaviors (Cepeda et al, 2008; Litman and Davachi, 2008), however, the extent to which this is true to motor learning has primarily been investigated in human subjects. Results have been mixed, with some studies showing a benefit of spaced training on motor learning (Kwon et al, 2015; Spruit et al, 2017) and some showing no benefit versus massed training (Nadeau et al, 2014; Wiseheart et al, 2017). The effect of spaced versus massed training and has never clearly been formally assessed for standard rodent rotarod learning, let alone motor gist learning.…”
Section: Discussionmentioning
confidence: 99%
“…Although the benefits of these strategies have mainly focused on improved knowledge acquisition and retention, evidence is growing that they also may be applied to attainment of psychomotor skills. 35,36 Spaced Learning. Repetition is a successful strategy for learning.…”
Section: Optimizing Knowledge Retentionmentioning
confidence: 99%
“…154 Distributed practice over time has been used to improve learning of surgical and resuscitative skills. 35,155,156 Both knowledge and skill acquisition are dependent on memory consolidation, and spacing allows this to occur. 157 The repetitive practice of several separate but related skills, as opposed to practicing one skill at a time until "mastery," may also improve the learning of psychomotor skills.…”
Section: Evidence-based Education In Anesthesiologymentioning
confidence: 99%
“…3,4,12,14,15 the disadvantage that, after prolonged periods of practice, the learner's ability to concentrate diminishes and that detrimental factors such as fatigue and boredom further affect the effectiveness of training. 2,17 This observation is known as reactive inhibition and has been demonstrated to negatively impact the learning of psychomotor skills. 18-21 A short rest of just ve minutes can already drastically attenuate the effect of reactive inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…3,18,21,22 Research showed that spaced training with breaks offering the opportunity to sleep (i.e., lying in a bed, reduced activity, reduction of visual-auditory input) were more effective than conventional massed training. 17 An alternative explanation for the superior results of spacing is that there is simply more time for psychomotor skills to be cognitively consolidated between training sessions. 3 Regardless of whether rest periods enhance skill acquisition through cognitive consolidation or by reducing reactive inhibition, trainees following spaced training patterns outperformed trainees following massed training despite identical training loads.…”
Section: Introductionmentioning
confidence: 99%